Inverse association between serum lipid profiles and hepatocellular carcinoma risk: a meta-analysis of epidemiological studies - Zeng, Chongshi; Liu, Shuran; Li, Haining; Han, Xiao (Frontiers in Oncology, 2025)
​BackgroundThe relationship between serum lipid profiles and hepatocellular carcinoma (HCC) risk remains controversial. We aimed to clarify this association through a systematic meta-analysis of epidemiological studies.​MethodsA systematic literature search was conducted in PubMed, Embase, and Web of Science (2000–May 2023) for prospective, retrospective, and cross-sectional studies reporting adjusted risk estimates (HR/OR) of HCC associated with serum lipids. Pooled effect sizes were calculated using random-effects models, with heterogeneity assessed via Cochran’s Q and I² statistics.​ResultsTwenty-three studies (16 cohorts, 7 case-control) involving 1.2 million participants ((including both healthy individuals and patients with chronic liver diseases)​​) were included. Elevated serum total cholesterol (TC) was inversely associated with HCC risk (HR = 0.71, 95% CI: 0.64–0.78; I²=0%). Similar protective effects were observed for high LDL (HR = 0.46, 95% CI: 0.36–0.59; I²=97%), triglycerides (HR = 0.79, 95% CI: 0.62–0.99; I²=94%), and dyslipidemia (HR = 0.64, 95% CI: 0.50–0.83; I²=81%). No significant association was found for high-density lipoprotein (HDL). Sensitivity analyses confirmed robustness for TC and LDL, while TG results were influenced by a single study.​ConclusionThis meta-analysis provides robust evidence that elevated serum cholesterol and specific lipid subfractions are associated with reduced HCC risk. Further mechanistic studies are warranted to elucidate the role of lipid metabolism in hepatocarcinogenesis.